Advection-Dispersion Equation for Concentrations of Pollutant and Dissolved Oxygen - Paudel, Keshav; Kafle, Jeevan; Bhandari, Prem Sagar (Journal of Nepal Mathematical Society, 2022)
A coupled system of advection-dispersion equations based water pollution model is presented that incorporates different parameters. The major concerns of the research are to observe the concentrations of pollutant and dissolved oxygen in the river. One dimensional model is used to observe the concentrations by taking the dimension along the length of the river. Since the processes of pollution and aeration are ongoing, the investigation of steady states is made possible by taking into account the elimination of pollutants by aeration. In this model coupled advection-dispersion equations are solved by taking dispersion coefficient as zero and non-zero, respectively.